IMMEDIATE IMPLANTATION AFTER EXTRACTION LASER ASSISTED PROTOCOL - Ionuţ Daniel Mihai; Roxana Mihai; Raluca Monica Comăneanu; Doina Lucia Ghergic (Amaltea Medical Publishing House, 2018)
Objectives. We have developed and applied an assisted laser immediate implantation protocol to accelerate postoperative healing and reduce the incidence of inflammatory or infectious complications. Material and method. After rigorous selection of patients who were candidates for immediate implantation, we applied to them an operator protocol that included the use of surgical guides, local assisted laser decontamination, atraumatic dental extraction with piezosurgery, immediate insertion of dental implants and postoperative biostimulation with laser. Results and discussion. We have exemplified the previously described operator protocol for a 58-year, non-smoker, and clinically healthy patient. Digital planning of treatment and guided insertion of implants has increased the precision of the act. The use of the piezosurgery for the dental extraction had a major role in preserving the bone of the patient. Also, laser decontamination and biostimulation reduced the incidence of postoperative complications and discomfort and hurried the wound healing. Conclusions. The patient had no complications of inflammatory or infectious in any postoperative control. The limits of the procedure are due to the increased cost of the necessary equipment and to the possible undesired effects of inappropriate laser irradiation carried out by inadequately trained specialists.